When do myopia genes have their effect? Comparison of genetic risks between children and adults. Issue 8 (9th September 2016) - Tideman, J. Willem L.; Fan, Qiao; Polling, Jan Roelof; Guo, Xiaobo; Yazar, Seyhan; Khawaja, Anthony; Höhn, René; Lu, Yi; Jaddoe, Vincent W.V.; Yamashiro, Kenji; Yoshikawa, Munemitsu; Gerhold‐Ay, Aslihan; et al.
ABSTRACT: Previous studies have identified many genetic loci for refractive error and myopia. We aimed to investigate the effect of these loci on ocular biometry as a function of age in children, adolescents, and adults. The study population consisted of three age groups identified from the international CREAM consortium: 5, 490 individuals aged <10 years; 5, 000 aged 10–25 years; and 16, 274 aged >25 years. All participants had undergone standard ophthalmic examination including measurements of axial length ( AL ) and corneal radius ( CR ). We examined the lead SNP at all 39 currently known genetic loci for refractive error identified from genome‐wide association studies (GWAS), as well as a combined genetic risk score (GRS). The beta coefficient for association between SNP genotype or GRS versus AL / CR was compared across the three age groups, adjusting for age, sex, and principal components. Analyses were Bonferroni‐corrected. In the age group <10 years, three loci ( GJD2, CHRNG, ZIC2 ) were associated with AL / CR . In the age group 10–25 years, four loci ( BMP2, KCNQ5, A2BP1, CACNA1D ) were associated; and in adults 20 loci were associated. Association with GRS increased with age; β = 0.0016 per risk allele ( P = 2 × 10 –8 ) in <10 years, 0.0033 ( P = 5 × 10 –15 ) in 10‐ to 25‐year‐olds, and 0.0048 ( P = 1 × 10 –72 ) in adults. Genes with strongest effects ( LAMA2, GJD2 ) had an early effect that increased with age. Our results provide insights on the age span during which myopia genes exert their effect. These insights form the basis for understanding the mechanisms underlying high and pathological myopia.